Far field microwave NDE of composite structures using time reversal mirror. (January 2018) - Mukherjee, Saptarshi; Tamburrino, Antonello; Haq, Mahmoodul; Udpa, Satish; Udpa, Lalita
Abstract: Microwave NDE techniques rely on the ability to propagate through Fiber Reinforced Polymer (FRP) composites and provide information about the structural integrity of composite materials. Time reversal (TR) property of the wave equation offers an effective method for interpreting the microwave NDE data. In TR, the fields back-propagate to focus at the source. TR techniques using microwave measurements have proved to be promising in radar imaging and nondestructive evaluation (NDE). This paper investigates the feasibility of using microwave TR for NDE of composite materials. Simulation studies demonstrate the feasibility and robustness of this approach to detect disbonds in metal-composite joints. An experimental system is built using a pulsed time domain setup coupled with the TR method. Experimental results demonstrate the capability of this technique for detecting single as well as multiple defects in composite materials.